Application of Nd2O3–Al2O3–SiO2 glass solder for joining of silicon carbide components. Issue 7 (June 2016) - Ahmad, S.; Herrmann, M.; Mahmoud, M.M.; Lippmann, W.; Hurtado, A.; Seifert, H.J.
Abstract: Glasses in the Nd2 O3 –Al2 O3 –SiO2 system were prepared using the melt–quench route. Thermal analyses of the prepared glasses were carried out to determine glass transition and crystallisation temperatures. The prepared glass showed surface crystallisation with no sign of bulk crystallisation. After long heat-treatment at 1200 °C for 50 h in argon atmosphere mullite, Nd-disilicate phases and an unknown crystalline phase were detected by XRD analysis. Furthermore, it was demonstrated that Nd-aluminosilicate glass can be used as solder for joining silicon carbide (SiC) components using laser-assisted process. The optimized used processing conditions produced joints with hermetic tightness (<1 × 10 −9  mbar l s −1 ) and an average 4-point bending strength of 150 MPa. Fracture analyses did not show fracture along the SiC/glass interface that indicates the good adhesion of the solder glass with SiC surface.